Review Sistematis Pengaruh Leverage terhadap Investasi, Dividen, dan Nilai Perusahaan - Atmanto, Dwi (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
This article discuss the influence of leverage on the investment, dividend and company value. Many theoretical debates related to the influence between these variables. Besides, some previous studies showed inconsistent results. Therefore, based on theory and several previous research models, this article proposes a concept model of the influence of leverage on the investment, dividends and company value.